2023
DOI: 10.3390/antibiotics12071203
|View full text |Cite
|
Sign up to set email alerts
|

Surveys on Pet-Reptile-Associated Multi-Drug-Resistant Salmonella spp. in the Timișoara Metropolitan Region—Western Romania

Abstract: The number of reptiles owned as pets has risen worldwide. Additionally, urban expansion has resulted in more significant human encroachment and interactions with the habitats of captive reptiles. Between May and October 2022, 48 reptiles from pet shops and 69 from households were sampled in the Timișoara metropolitan area (western Romania). Three different sample types were collected from each reptile: oral cavity, skin, and cloacal swabs. Salmonella identification was based on ISO 6579-1:2017 (Annex D), a mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…The study of Cristina et al ( 2022 ) determined E. faecalis as the most frequently isolated species; however, their study included 25 sick reptiles with no response to treatment. The identification of the Salmonella genus in Elaphe schrenckii confirms the fact that reptiles are well-known reservoir of Salmonella , species as previous studies also demonstrated (Zajac et al 2021 ; Dégi et al 2023 ). These poikilothermic vertebrates can be easily colonised with vertical and horizontal transfer and shed pathogens intermittently (Schroter et al 2006 ).…”
Section: Discussionsupporting
confidence: 82%
“…The study of Cristina et al ( 2022 ) determined E. faecalis as the most frequently isolated species; however, their study included 25 sick reptiles with no response to treatment. The identification of the Salmonella genus in Elaphe schrenckii confirms the fact that reptiles are well-known reservoir of Salmonella , species as previous studies also demonstrated (Zajac et al 2021 ; Dégi et al 2023 ). These poikilothermic vertebrates can be easily colonised with vertical and horizontal transfer and shed pathogens intermittently (Schroter et al 2006 ).…”
Section: Discussionsupporting
confidence: 82%